Analysis of DPR Policy in Rejecting the Transfer of the Capital City of Jakarta to the Capital of Nusantara - Hamid Noor Yasin; Megawati Barthos (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
The relocation of Jakarta's capital to the National Capital Region (IKN) has sparked a heated debate in public policy circles. This article delves into the reasons why the House of Representatives (DPR) rejected the proposal, highlighting several key factors. The financial aspect was a major concern, given the high cost of building new infrastructure in IKN Nusantara, particularly in light of limited state funds and other development priorities. The social impact was also an important consideration, as population displacement, changes in lifestyle, and economic uncertainty were among the many potential consequences of moving the capital. Additionally, environmental issues such as ecosystem damage and increased pollution were also significant points of concern. Political stability was another crucial factor in the DPR's decision, as the potential disruption to stability caused by the move would need to be carefully assessed. The DPR has emphasized the importance of broad public consultation to ensure that any proposed relocation is supported by the community. An article highlights South Africa's successful capital relocation as an example of effective planning, strong public participation, and the resolution of infrastructure issues. These remarks can be applied to the Indonesian context to achieve a successful relocation.